Gemma-2-7B vs. Mistral-7B and Llama-2-7B in Mathematical Reasoning on BIG-Bench - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 11 peer-reviewed papers addressing the following research question: How does the mathematical reasoning performance of Gemma-2-7B compare to Mistral-7B and Llama-2-7B on BIG-Bench subsets when controlling for instruction finetuning scale. 8 claims were extracted from source literature; 7 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 8.1/10. This report is a machine-generated litera
Machine-generated literature synthesis.